Pemodelan Pengaruh Kemiskinan dan Covid-19 Terhadap Ketahanan Pangan Kabupaten Bandung dengan GWR (Geograpichally Weight Regression) - Syakirotin, Muthiah; Karyani, Tuti; Noor, Trisna Insan (Universitas Galuh, 2025)
The Covid-19 pandemic has had an impact on changes in community economic activity, resulting in an impetus for increasing poverty rates (BPS, 2020). This happens because of the community's space for movement so that it has an impact on the community's ability to obtain safe and sufficient food. Based on the 2020 Food Security Index, most districts in West Java are in a very resilient status. The status of food security at the provincial or city/district scale does not always guarantee that every individual is food secure because each region has different characteristics. Therefore, it is necessary to study the model of the influence of the proportion of poverty and the proportion of the population infected with Covid-19 on food security in Bandung Regency to the village level. This study aims to model the effect of the proportion of poverty and the proportion of the population infected with Covid-19 on the resilience of Bandung Regency using Geographically Weight Regression (GWR), which is a geographically weighted regression. Based on the analysis of the model of the effect of the proportion of the population infected with Covid-19 and poverty on food security in Bandung Regency, there are 280 different GWR models. In the GWR model the effect of the proportion of the population infected with Covid-19 on food security, there are 40 villages in red (high influence) and 15 villages in green (low influence). The village that has the highest influence on the proportion of the population infected with Covid-19 is Nengkelan Village with a coefficient of 21.02323822 and Laksana Village has the lowest effect with a coefficient of -18.760392. While the GWR model of the effect of poverty on food security is found in 9 villages in red color and 4 villages in green color. The village with the highest influence is Cipelah Village with a coefficient of 0.661185245 while the village with the lowest influence is Sukaresmi Village with a coefficient of -2.667401414.